The role of applying internal and external auditing methods in reducing the phenomenon of money laundering - Rhaif, Saad Abed; rekan radhi, Saher; Kareem, Dhurgham Aseal; Fnayek, Mustafa Naeem (South Asian Journal of Social Sciences and Humanities, 2024)
This research aimed to use modern methods in internal and external auditing and its implications for combating money laundering and conducted a theoretical study and a field study. The study included a quantitative analysis of the data of commercial banks in the capital of the study country, Baghdad, which included seven commercial banks. The research sample included a group of 250 individuals working in these banks. The data were processed using statistical methods using the SPSS programme. The results of the statistical evaluation of the data collected using a specially prepared survey tool showed that there is an effect and a correlation between the dimensions of criminal accounting (internal audit, external audit, reasons for money laundering, the perfect effect, consulting intellectual, considerations of individuality) and variable dependent money laundering, and the availability of a set of characteristics, knowledge, and skills that help the accountant or chequer combat or contain money laundering operations. There are several methods and procedures used by it chequers to combat or have money laundering operations.